2018
DOI: 10.1016/j.tipsro.2018.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of intra-fraction prostate motion – Determining optimal bladder volume and filling for prostate radiotherapy using daily 4D TPUS and CBCT

Abstract: Background and purpose: Inconsistent bladder and rectal volumes have been associated with motion uncertainties during prostate radiotherapy. This study investigates the impact of these volumes to determine the optimal bladder volume. Materials and methods: 60 patients from two Asian hospitals were recruited prospectively. 1887 daily cone-beam computed tomography (CBCT) images were analysed. Intra-fraction motion of the prostate was monitored real-time using a four-dimension transperineal ultrasound (4D TPUS) C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…While the prostate is shifted anteriorly in most cases as the bladder volume is reduced, in some cases, posterior shift is observed. These findings match the results of a recent study based on analysis of CBCT and four‐dimensional (4D) trans‐perineal ultrasound (4D TPUS) measurements of 60 patients that showed intra‐fractional motion of the prostate in the A‐P and S‐I directions . In this study, reduction of A‐P motion of the prostate was observed when the planned bladder volume was greater than 200 ml.…”
Section: Discussionsupporting
confidence: 90%
“…While the prostate is shifted anteriorly in most cases as the bladder volume is reduced, in some cases, posterior shift is observed. These findings match the results of a recent study based on analysis of CBCT and four‐dimensional (4D) trans‐perineal ultrasound (4D TPUS) measurements of 60 patients that showed intra‐fractional motion of the prostate in the A‐P and S‐I directions . In this study, reduction of A‐P motion of the prostate was observed when the planned bladder volume was greater than 200 ml.…”
Section: Discussionsupporting
confidence: 90%
“…Ensure adequate bladder filling (>200 cm 3 ) (practice is dependent on departmental workflow). 13 8. Reduce the time lapse between the CT/TPUS images by acquiring the TPUS images immediately before or immediately after the final CT scan to avoid gross movement which may affect subsequent registration of the CT/TPUS images.…”
Section: Perform a Cone-down Volume Of The Ct Scan To Checkmentioning
confidence: 99%
“…In addition, the impact of UV changes on prostate position during radiotherapy is not commonly agreed on. Some studies have concluded that the UV changes during treatment correlated with the displacement of the prostate [7][8][9][10][11][12], while others found no such correlation [4,[17][18][19]. We hypothesized that the prostate volume (PV) could also be related to the susceptibility of prostate movement due to changes in UV, however, there is no report of details of this relationship.…”
Section: Introductionmentioning
confidence: 96%
“…One of the main factors in the changes of the position of the prostate during radiotherapy is the change in urinary volume (UV) in the bladder [7][8][9][10][11][12]. Considerations to keep UV constant during radiotherapy are widely recommended [6,[13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%